Preparation and In-Vitro Evaluation of Clopidogrel Bisulfate Liquisolid Compact - Mohammed, Amina M.; Mohammed, Entidhar J. (Iraqi Journal of Pharmaceutical Sciences, 2018)
Liquisolid compact is the most promising technique for increasing dissolution rate and bioavailability of poorly soluble drugs.Clopidogrel bisulfate is an oral antiplatelets used for treatment and prophylaxis of cardiovacular and peripheral vascular diseases related to platelets aggreagation.Clopidogrel has low solubility at high pH media of intestine and low bioavailability of a bout 50% after oral doses.The purpose of this work was to enhance dissolution pattern of clopidogrel through its formulation into liquisolid tablets.A mathematical model was used to calculate the optimum quantities of tween 80 , carrier (Avicel PH 102) and coating material (Aerosil 200) needed to prepare acceptably flowing and compactible powder mixtures.The liquisolid tablets were evaluated for hardness, percent friability, weight variation, content uniformity , disintegration time and in vitro drug release profile.DSC , FTIR , XRD and SEM were used for assessment of physicochemical properties of drug and compatibility with excipients in the liquisolid compacts.The selected formulation (F2) released 92.2% of its content during first 10 min. compared to 13.6% of directly compressed tablet and 24.2% of marketed tablet. In conclusion the dissolution rate and bioavailability of clopidogrel can be enhanced to a great extent by liquisolid technique.